Meningkatkan Sikap Religius Melalui Pembiasaan Membaca Surat Al-Waqiah Pada Siswa Kelas VIII di Al-Mubarok Serang - Euis Ismayati Yuniar; Ahmad Wahyudin; Reza Umami (KRAKATAU (Indonesian of Multidisciplinary Journals), 2023)
This study aims to improve religious attitudes through the habit of reading Al-Waqiah letters in class VIII students at Al-Mubarok Serang. This research method uses a qualitative approach, namely analyzing a problem by reviewing it from the side of objective, expressive and documentary meanings. The collection of data used is participatory interviews and observation. While the technique used to analyze the data in this study using a qualitative descriptive analysis method. The results of this study are as follows: first, reading the letter Al-waqiah at the Al-Mubarok Serang Islamic boarding school is read regularly every day after the dawn prayer to motivate the reader to get a lot of fadhilah in it. Second, the objective meaning of reading Surah Al-Waqiah is that this tradition has been carried out and with the aim of making students/santri become pious and pious students. Meanwhile, the expressive meaning of reading Surah Al-Waqi'ah can provide relief in times of trouble, ease in solving problems, and easy in obtaining sustenance. As for the documentary meaning, students can become people who are disciplined in religion, especially those related to Allah SWT (hablum minallah) and also with fellow human beings (hablum minannas) so that from a practice of using the verses of the Qur'an it can become a whole culture. So it can be concluded that getting used to reading Al-Waqiah's letter can improve religious attitudes in class VIII students at Al-Mubarok Serang